The Determinants Of Ownership Structure In Malaysia. - Ei, Yet Chu; Cheah, Kooi Guan (2004)
The paper examines the determinants of ownership structure characteristics of the 147 main board firms listed on the Kuala Lumpur Stock Exchange (KLSE). We apply nature of the firm theory :- asymmetric information, agency conflicts and risk as discussed in Putterman (1993). Ownership concentration is divided into dispersed, dominant minority, and majority controlled firms.